2005
DOI: 10.1182/blood-2004-10-4113
|View full text |Cite
|
Sign up to set email alerts
|

NK-cell reconstitution after haploidentical hematopoietic stem-cell transplantations: immaturity of NK cells and inhibitory effect of NKG2A override GvL effect

Abstract: Natural killer (NK) cell alloreactivity is reported to mediate strong GvL (graft versus leukemia) effect in patients after haploidentical stem-cell transplantation (SCT) for acute myeloid leukemia (AML). Because subsequent immune reconstitution remains a major concern, we studied NK-cell recovery in 10 patients with AML who received haplomismatched SC transplants, among whom no GvL effect was observed, despite the mismatched immunoglobulin-like receptor (KIR) ligand in the GvH direction for 8 of 10 patients. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
208
5
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(243 citation statements)
references
References 45 publications
24
208
5
6
Order By: Relevance
“…This observation was true for samples with group A as well as group B haplotypes (data not shown). These data, together with previous observations of clinical NK cell reconstitution (20,21), suggest a model of sequential order of KIR expression for the HLA-C-specific inhibitory KIR that might be genetically predetermined (Fig. 4).…”
Section: Sequential Acquisition Of Hla-c-specific Inhibitory Kirsupporting
confidence: 78%
“…This observation was true for samples with group A as well as group B haplotypes (data not shown). These data, together with previous observations of clinical NK cell reconstitution (20,21), suggest a model of sequential order of KIR expression for the HLA-C-specific inhibitory KIR that might be genetically predetermined (Fig. 4).…”
Section: Sequential Acquisition Of Hla-c-specific Inhibitory Kirsupporting
confidence: 78%
“…39 Another NK cell escape mechanism demonstrated in the HSCT setting is the overexpression of the inhibitory receptor CD94/ NKG2A on reconstituted NK cells that recognizes human leukocyte antigen-E on AML blasts, which is associated with a low cytotoxic capacity. 40,41 AML cells themselves contribute to impaired NK cell-mediated killing by decreased or absent expression of surface ligands for various NK cell activating receptors, including NCRs and NKG2D. 27,28,42,43 Furthermore, AML cells can shed ligands for NKG2D, as demonstrated by the increased serum levels of MHC class I chain-related genes A and B (MICA/B) in AML patients compared with healthy controls.…”
Section: How Aml Evades Nk Cell Immune Surveillancementioning
confidence: 99%
“…[45][46][47] NK CELL-DIRECTED THERAPIES FOR AML The success of NK cell-directed immunotherapy involves the functionality of the reconstituted NK cell compartment of patients in complete remission post (standard) therapy. Several studies have demonstrated that the NK cell compartment recovers rapidly, but is accompanied with a skewing of cell subsets towards CD56 bright (that is, immature) NK cells (post HSCT 40,41,[74][75][76][77] or post consolidation chemotherapy 78 ), in some cases potently impairing the graft-versus-leukemia effect (for example, overexpression of the inhibitory receptor CD94/NKG2A was associated with impaired cytotoxicity 40,41 ). Therefore, it has been proposed that early modulation of NK cell immunity could improve therapy-related outcome.…”
Section: Nk Cell Immune Escape In Aml E Lion Et Almentioning
confidence: 99%
“…In comparison with transplants from adult donors, UCB transplants offer the advantage of prompt availability for many recipients and a decreased risk of graft-versus-host disease (GVHD) [2,3], but such transplants are associated with a slower hematological and immune recovery, leading to a higher risk of infection [4,5]. Mismatched-unrelated donor transplants are associated in some studies with a lower risk of relapse, but a higher risk of GVHD [6,7], while haploidentical HSCT may be complicated by a high risk of relapse and delayed immune recovery [8][9][10].…”
Section: Introductionmentioning
confidence: 99%